PETROLOGY AND ORIGIN OF AMOEBOID OLIVINE AGGREGATES IN CR CHONDRITES - Weisberg M.K.; Connolly Jr.H.C.; Ebel D.S. (My University, 2004)
Amoeboid olivine aggregates (AOAs) are irregularly shaped, fine‐grained aggregates of olivine and Ca, Al‐rich minerals and are important primitive components of CR chondrites. The AOAs in CR chondrites contain FeNi metal, and some AOAs contain Mn‐rich forsterite with up to 0.7 MnO and Mn:Fe ratios greater than one. Additionally, AOAs in the CR chondrites do not contain secondary phases (nepheline and fayalitic olivine) that are found in AOAs in some CV chondrites. The AOAs in CR chondrites record a complex petrogenetic history that included nebular gas‐solid condensation, reaction of minerals with the nebular gas, small degrees of melting, and sintering of the assemblage. A condensation origin for the Mn‐rich forsterite is proposed. The Mn‐rich forsterite found in IDPs, unequilibrated ordinary chondrite matrix, and AOAs in CR chondrites may have had a similar origin.